1999
DOI: 10.1016/s1074-7613(00)80020-5
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S Required for Normal MHC Class II Peptide Loading and Germinal Center Development

Abstract: Major histocompatibility complex (MHC) class II molecules acquire antigenic peptides after degradation of the invariant chain (Ii), an MHC class II-associated protein that otherwise blocks peptide binding. Antigen-presenting cells of mice that lack the protease cathepsin S fail to process Ii beyond a 10 kDa fragment, resulting in delayed peptide loading and accumulation of cell surface MHC class II/10 kDa Ii complexes. Although cathepsin S-deficient mice have normal numbers of B and T cells and normal IgE resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
427
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 477 publications
(445 citation statements)
references
References 38 publications
15
427
0
2
Order By: Relevance
“…16,17 Both of them have been implicated in the last step of the degradation of invariant chain, a key process in MHC class II antigen presentation, 18 and play a major role in the control of the immune response and autoimmunity. 19 Indeed, the use of cathepsin S inhibitors prevents disease in a murine model for Sjö gren syndrome, 20 and cathepsin V is upregulated in the thymus from MG patients. 17 PRSS16 is a recently described serine protease that is also expressed exclusively in the thymic cortex, 1 exactly where the events leading to positive selection take place.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Both of them have been implicated in the last step of the degradation of invariant chain, a key process in MHC class II antigen presentation, 18 and play a major role in the control of the immune response and autoimmunity. 19 Indeed, the use of cathepsin S inhibitors prevents disease in a murine model for Sjö gren syndrome, 20 and cathepsin V is upregulated in the thymus from MG patients. 17 PRSS16 is a recently described serine protease that is also expressed exclusively in the thymic cortex, 1 exactly where the events leading to positive selection take place.…”
Section: Discussionmentioning
confidence: 99%
“…The immune cells (B cells, T cells, dendritic cells and macrophages) of the rheumatoid pannus are believed to be involved in antigen presentation, antibody production and cytokine generation. An important role in antigen presentation has been identified for cathepsin S, which is involved in both the processing of endocytosed proteins to peptides suitable for presentation and the cleavage of the invariant chain to CLIP during MHC class II maturation (Riese et al, 1996;Shi et al, 1999;Villadangos et al, 1999). Studies of cathepsin S knockout mice revealed a decrease in their susceptibility to collagen-induced arthritis and impaired invariant chain processing in both dendritic cells and B cells (Nakagawa, Brissette et al, 1999).…”
Section: Synovium: Inflammation Hyperplasia Pannus Formation and Prmentioning
confidence: 99%
“…Cleavage of a 10 kDa CD74 fragment, p10, is performed in most APCs preferentially by the cysteine endopeptidase cathepsin S and seems to be the most critical step in the final generation of CLIP. 23,24 Loading of the MHC class II with 10-30 amino-acid long antigenic peptides is known to take place in the so-called MHC class II loading compartment with the help of other accessory molecules such as the human leukocyte antigen DM (HLA-DM). 14,22 The final step in the expression of MHC class II is its transport to the cell surface.…”
mentioning
confidence: 99%
“…Individual data obtained from six donors are indicated. (b) Monocytes were isolated from PBMCs before (0 h), during (12 h) and after (24,48,and 72 h) priming period. Monocyte legumain expressions are given from duplicate measurements from one experiment (mean7range).…”
mentioning
confidence: 99%
See 1 more Smart Citation